2023
DOI: 10.1128/jvi.01463-22
|View full text |Cite
|
Sign up to set email alerts
|

Single Particle Analysis of H3N2 Influenza Entry Differentiates the Impact of the Sialic Acids (Neu5Ac and Neu5Gc) on Virus Binding and Membrane Fusion

Abstract: Influenza A virus (IAV) infections continue to threaten human health, causing over 300,000 deaths yearly. IAV infection is initiated by the binding of influenza glycoprotein hemagglutinin (HA) to host cell sialic acids (Sias) and the subsequent viral-host membrane fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Our experiments, showing the effect of V/HN-LV infection on both desialylated HEK293FT cells and monkey CMAH-overexpressing HEK293FT cells, revealed that SeV-HN proteins preferentially utilize Neu5Ac to support viral entry into host cells. For influenza viruses, a similar pattern was reported, which was that Neu5Gc terminated glycoconjugates act as a decoy or low-binding receptor for the hemagglutinin (HA) domain [61,62]. We also observed that V/HN-LV transduction efficiency was decreased by neuraminidase inhibitor 2,3-dehydro-2-deoxy-N-acetylneuraminic acid (DANA) treatment, which suggests the relative contribution of the neuraminidase of SeV-HN for the viral entry.…”
Section: Discussionsupporting
confidence: 81%
“…Our experiments, showing the effect of V/HN-LV infection on both desialylated HEK293FT cells and monkey CMAH-overexpressing HEK293FT cells, revealed that SeV-HN proteins preferentially utilize Neu5Ac to support viral entry into host cells. For influenza viruses, a similar pattern was reported, which was that Neu5Gc terminated glycoconjugates act as a decoy or low-binding receptor for the hemagglutinin (HA) domain [61,62]. We also observed that V/HN-LV transduction efficiency was decreased by neuraminidase inhibitor 2,3-dehydro-2-deoxy-N-acetylneuraminic acid (DANA) treatment, which suggests the relative contribution of the neuraminidase of SeV-HN for the viral entry.…”
Section: Discussionsupporting
confidence: 81%
“…Equine IAVs are the only IAVs that have a higher preference for Neu5Gc than Neu5Ac ( Broszeit, 2019 ; Gambaryan et al., 2012 ) however, a single amino acid substitution can improve the binding preference for Neu5Gc in IAV isolates from turkeys, chickens, and dogs ( Spruit et al., 2022 ; Wen et al., 2018 ). Furthermore, a recent study showed that a change of binding affinity from Neu5Ac to Neu5Gc does not affect the fusion of IAV with the endosomal membrane because the fusion is only dependent on the H2 subunit ( Chien, 2023 ). The difference in SA preference between avian IAV isolates (SA-α2,3) and the human or swine IAV isolates (SA-α2,6) constitute one of the most important species barriers between IAV in birds and mammalians ( Bourret, 2018 ), but since human and swine IAV isolates have a similar preference for the SA-α2,6 receptor, this cannot explain why most swine-adapted IAVs have a decreased ability to infect humans.…”
Section: Introductionmentioning
confidence: 99%